Foreign Aids and Sustainable Development in Nigeria: An Application of Dynamic Least Squares Approach - Falade A. Olufemi Olusegun (ORGANIZE: Journal of Economics, Management and Finance, 2023)
The impact of foreign aid in donor and recipient countries is largely unsettled amongst existing studies, as well as, literature. This is attributed to the various arguments for and against the benefits of foreign aid, as it relates to sustainable development. As such, the study examined the effect of foreign aids on sustainable development in Nigeria from 1986-2021. The study used Augmented Dickey Fuller (ADF) unit root test, Johansen Co-integration test, Dynamic Least Squares (DOLS) and Granger Causality test. The ADF result showed that sustainable development, foreign aids, exchange rate, inflation rate and trade openness were stationary at first level difference. Also Johansen co-integration test confirmed a long-run relationship between the variables. The DOLS result revealed that, foreign aid, exchange rate and trade openness were significant with each exhibiting a direct link with sustainable development at 5%; while, that of foreign aid was at 10%. This suggests that inflow of foreign aids in different forms is essential for resource conservation. Also, inflation rate showed an inverse and significant link with sustainable development at 5%. In addition, a bi-directional causality was established between foreign aid and sustainable development. The study concluded that foreign aids in different forms, exchange rates stability and high exportation that comply with environmental sustainability boost Nigeria's sustainable development growth, but spiral inflation worsens it. Thus, it is advised that government should declare an emergency over environmental issues in order to guarantee an increase in the flow of foreign aid into environmental sustainability.